Through the Pandemic Portal: Turning to Community to Cultivate a Relational Paradigm of Leadership - Ishimaru, Ann; B. Craig, Anthony; Daw, Constance E.; Jackson, William (Revista Saberes Educativos, 2025)
The global pandemic opened a portal for a different paradigm of educational leadership to emerge. Reaching beyond critique of the conventional, color-evasive leadership research and practice, we share how our leadership of a systems-focused preparation program turned to ancestral knowledges, relationality, and cultural practices embedded in Indigenous, Black and other communities of color to lead possible transformative futures with the youth and families owed a profound educational debt. The program shift enabled the practitioner leadership students to take up their leadership as a humanizing, liberatory practice that works toward familial relations with their students and families. We frame this journey “through the portal” and share excerpts from the public pedagogy of two students as they build from their own experiences as Black leaders who do not simply resist or fight unjust systems, but who also dream and live justice with young people and their families through education